Use of methods of wave processes modeling for control of defectiveness of non-metallic materials - Fursa T. V. Tatyana Viktorovna; Lyukshin B. A.; Utsyn G. E. Grigoriy Evgenievich; Kuimova M. V. Marina Valerievna (2014, 2014)
Title screen